The Human Capital in Seloka Pak Kaduk - Nazilah, Mohamad; Nor Hasimah, Ismail (2017)
Seloka is one of the traditional Malay poems which is a complete union of content or idea as a kind of poem that contains teachings such as sarcasm and jokes. In terms of the form of a seloka contains two, four or more lines. Seloka content usually consists of sharp satirical messages. Human capital can be interpreted to three important aspects, that is an excellent aspect of character, a strong and integrity principle and philosophy. Integrity is a visionary, structured design and polite treatment. The development of human capital should be given due attention, because quality human capital is an important element in the achievement of national missions should be done holisticall. There are several values in Seloka Pak Kaduk that can help build the soul and the individual and external aspects of an individual. The acquired human capital is able to produce people who think rationally, creative and critical.